2012
DOI: 10.1038/bjc.2012.346
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases in Asian HER2-positive breast cancer patients: anti-HER2 treatments and their impact on survival

Abstract: Background:In Asia, large-scale studies on anti-HER2 treatment in HER2-positive breast cancer patients with brain metastases are limited. We studied the treatment patterns of these patients in Asia to evaluate the impact of anti-HER2 treatment on the time to occurrence of brain metastases (TTBM) and survival after brain metastasis (BM).Methods:A retrospective study of HER2-positive breast cancer patients diagnosed with BM between January 2006 and December 2008 in six Asian countries was conducted. Demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 39 publications
5
57
0
5
Order By: Relevance
“…Özellikle bizim çalışmamızda da görüldüğü gibi akciğer, karaciğer ve beyin metastazı yapmaya eğilim söz konusudur. Her2 pozitif hastalarda bizim hastalarda olduğu gibi ilk olarak beyin metastazının ortaya çık-ması azımsanmayacak sıklıktadır (18). Her2 pozitif tümörlerin daha sık beyin metastazı yapmasının nedeni tam olarak anlaşılamamış olsa da monoklonal antikorların kan-beyin bariyerini geçememesine veya bu anatomik bölgede reseptör blokajını tam olarak gerçekleştirememe-sine bağlı olabildiği düşünülmektedir.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Özellikle bizim çalışmamızda da görüldüğü gibi akciğer, karaciğer ve beyin metastazı yapmaya eğilim söz konusudur. Her2 pozitif hastalarda bizim hastalarda olduğu gibi ilk olarak beyin metastazının ortaya çık-ması azımsanmayacak sıklıktadır (18). Her2 pozitif tümörlerin daha sık beyin metastazı yapmasının nedeni tam olarak anlaşılamamış olsa da monoklonal antikorların kan-beyin bariyerini geçememesine veya bu anatomik bölgede reseptör blokajını tam olarak gerçekleştirememe-sine bağlı olabildiği düşünülmektedir.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Эта концепция была подтверждена в ряде исследований [26,27]. Кроме того, несколько клини-ческих исследований показали, что сочетание химио-терапии с трастузумабом повышает выживаемость даже после развития метастазов в ГМ [28,29]. Это пре-имущество, как предполагают, в основном обусловле-но улучшением контроля системного заболевания [30].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…The analysis demonstrated that lapatinib plus capecitabine treatment was associated with a lower rate of brain tumor progression, compared with capecitabine alone (65). This finding led to several trials of patients with brain metastases treated with lapatinib, with the results suggesting that lapatinib plays a role in the prevention and management of brain metastases in patients with HER2-positive breast cancer (66)(67)(68).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%